A diagnostic dilemma of sclerosing odontogenic carcinoma: case report. Issue 2 (March 2022) - Oya, Kaori; Tsuji, Tadataka; Nakatani, Atsutoshi; Hiraoka, Shin-ichiro; Usami, Yu; Fukuda, Yasuo; Kishino, Mitsunobu; Toyosawa, Satoru
Abstract: We report a case of a fibrous odontogenic lesion occurring in the maxilla of a man in his 60s. The patient presented with an asymptomatic radiolucent area related to the upper left premolar on radiography. Histological examination of the lesion obtained through an incisional biopsy revealed dense fibrous connective tissue containing small, rounded islands of odontogenic epithelium. The differential diagnoses included central odontogenic fibroma and sclerosing odontogenic carcinoma. Despite being completely different entities, the histological similarities between the two tumors raise diagnostic challenges, with fibrous connective tissue and odontogenic epithelium being the common features. Owing to the finding of unclear small or thin epithelial nests with a high nuclear-cytoplasmic ratio and despite its small size, the lesion was suspected of being malignant, and a maxillary resection was performed. Sections from the resected specimen displayed a small or tiny odontogenic epithelium with cellular atypia and invasion by epithelial cells in and around the nerve fasciculi; therefore, a final diagnosis of sclerosing odontogenic carcinoma was made. Nonetheless, the presence of an odontogenic epithelium in or around the nerve fascicles is not always an evidence of malignancy in the jaw. Caution should be exercised when differentiating invasive epithelia from epithelial residues to provide appropriate treatment.